2016
DOI: 10.18632/oncotarget.8721
|View full text |Cite
|
Sign up to set email alerts
|

The Mbd4 DNA glycosylase protects mice from inflammation-driven colon cancer and tissue injury

Abstract: Much of the global cancer burden is associated with longstanding inflammation accompanied by release of DNA-damaging reactive oxygen and nitrogen species. Here, we report that the Mbd4 DNA glycosylase is protective in the azoxymethane/dextran sodium sulfate (AOM/DSS) mouse model of inflammation-driven colon cancer. Mbd4 excises T and U from T:G and U:G mismatches caused by deamination of 5-methylcytosine and cytosine. Since the rate of deamination is higher in inflamed tissues, we investigated the role of Mbd4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 69 publications
(80 reference statements)
1
8
0
Order By: Relevance
“…In LUAD2, private mutations dominated by a signature for deamination of 5-mC (Fig. 6 ) were associated with germline variants in two genes functionally implicated in the repair of these mutations, MDB4 [ 25 ] and RPA1 [ 26 ] (Fig. 6 ; Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In LUAD2, private mutations dominated by a signature for deamination of 5-mC (Fig. 6 ) were associated with germline variants in two genes functionally implicated in the repair of these mutations, MDB4 [ 25 ] and RPA1 [ 26 ] (Fig. 6 ; Supplementary Table S3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of the pathways involved in AAG-induced retinal degeneration revealed potentially translatable therapeutic approaches (Allocca et al, 2019). Similarly, it has been reported that ischemic injury is less severe (Ebrahimkhani et al, 2014), and inflammation can be reduced (Yu et al, 2016) in DNA glycosylase-deficient cells. The data presented here demonstrate improved survival of DA neurons in old PD nematodes in the absence of exposure to DNA-damaging agents.…”
Section: Discussionmentioning
confidence: 98%
“…Second, studies from the Samson laboratory have demonstrated that DNA damage from inflammation drives mutations as well as cancer development (23,359). In one such study, mice lacking the BER glycosylase Aag were treated with a common colitis model of DSS in drinking water.…”
Section: Inflammation ←→ Dna Damage → Mutations → Cancermentioning
confidence: 99%